A dignidade humana no pensamento de Jeremy Waldron - Brito, Cynthia Lays Feitosa de (2022)
This work had the scope of presenting the work of Jeremy Waldron about human dignity. Care was taken to expose the author's conceptual proposal of dignity, understood as a legal status that refers to the ancient and historical notions of position (rank) and function (role), which were united with the modern conception of dignity, becoming together a leading concept and contributing enormously to an egalitarian theory of rights. Then, it was the accurate waldronian analysis about the idea that dignity is the foundation of human rights, demonstrating that the author scrutinizes the obstacles faced by the thesis, investigates what the proposition effectively means and tries, ultimately , clarify the role of dignity in human rights theory. Finally, the elements of distinctive value of dignity were clarified, through the review of decisions by higher courts and constitutional courts, carried out by Waldron (2018), in which the term would have added a value of its own to the legal arguments in which it appeared.